2000
DOI: 10.1021/jo0006829
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereo- and Regioselective Allylations Catalyzed by Mo−Pyridylamide Complexes:  Electronic and Steric Effects of the Ligand

Abstract: carboxylic acid esterscarboxylic acid esters (benzene compounds) Q 0530 -093Highly Stereo-and Regioselective Allylations Catalyzed by Mo-Pyridylamide Complexes: Electronic and Steric Effects of the Ligand.-The amide shown in entry D) containing electron-donating substituted pyridine rings is found to be an efficient ligand for the regio-and stereoselective allylation of the malonate (II). The use of ligands bearing electron-withdrawing substituted pyridine rings or alkyl substituted pyridine rings results in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Nucleophilic attack at the carbon bearing the leaving group has also been documented with Ru (48) and Fe (44) catalysts. On the other hand, Ni (27)(28)(29)(30)(31)(32)(33), Pd (19)(20)(21), and Pt (34,35) all typically produce a mixture of regioisomeric products, whereas Ir (37-43), Mo (22)(23)(24)(25)(26), and W (50) favor attack at the more highly substituted allylic terminus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleophilic attack at the carbon bearing the leaving group has also been documented with Ru (48) and Fe (44) catalysts. On the other hand, Ni (27)(28)(29)(30)(31)(32)(33), Pd (19)(20)(21), and Pt (34,35) all typically produce a mixture of regioisomeric products, whereas Ir (37-43), Mo (22)(23)(24)(25)(26), and W (50) favor attack at the more highly substituted allylic terminus.…”
Section: Discussionmentioning
confidence: 99%
“…19 and 20 and references therein and ref. 21), Mo (22)(23)(24)(25)(26), Ni (27)(28)(29)(30)(31)(32)(33), Pt (ref. 34 and references therein and ref.…”
mentioning
confidence: 99%
“…Despite these limitations, a number of very impressive enantioselective reactions involving chiral transition-metal complexes have been described. The research groups of Moberg, Hallberg, and Larhed reported on microwave-mediated palladium- [115,116] and molybdenum-catalyzed [117][118][119] asymmetric allylic alkylation reactions involving neutral carbon, nitrogen, and oxygen nucelophiles in 2000. Both processes were carried out under non-inert conditions and yielded the desired products in high chemical yield and with typical ee values of > 98 %.…”
Section: Asymmetric Allylic Alkylationsmentioning
confidence: 99%
“…As one part of ligand design, the modification of ligands at proper positions is important when a privileged ligand structure has been found, for the information on the structure-activity relationship obtained during this research process can direct the design of novel catalysts with enhanced efficiency. Besides the tuning of ligand steric effect which affects the selectivity of the catalytic process more directly, tuning of electronic effect has attracted more attention from the science community during recent years [1][2][3][4][5][6][7][8][9][10][11][12][13] . Not only the coordination ability of the ligands and the electronic density on the metal centers can be tuned, but also the inversion of the diastereoselectivity can be observed sometimes [12,13] .…”
Section: Introductionmentioning
confidence: 99%